Does exposure to child abuse at home increase the risk of child sexual abuse in 12-16-year-olds in Finland? - Kinnunen, Ida (My University, 2025)
This study examines whether physical, emotional, witnessed, and sibling violence at home increases the risk of child sexual abuse among 12–16-year-olds in Finland. The data comes from the 2022 Child Victim Survey, which is the third nationally representative study on violence experienced by sixth- and ninth-grade students in Finland. Students completed an online questionnaire during the school day, asking about victimization experiences at home, school, hobbies, and in their free time (Mielityinen et al. 2023). Previous research has relied largely on adults’ retrospective reports, and only limited research has been conducted directly with children to investigate their victimization experiences (Felitti et al. 1998; Ports et al. 2016; Andersen et al. 2024). The present study is also significant in that it examines potential risk factors for later sexual victimization using multiple well-known covariates to assess the true risk associated with childhood violence. The theoretical framework is based on the ACE theory by Felitti et al. (1998), which focuses on how experiences of violence, neglect, and family adversity increase the risk of later health and well-being problems. According to the theory, the greater the number of adverse experiences a child has, the higher the likelihood of long-term problems. Earlier retrospective studies have found that violence in the home increases the risk of sexual abuse (Dong et al. 2003; Finkelhor et al. 2007b; Zurbriggen et al. 2010; Briere et al. 2020). Studies conducted with children have similarly reported that violence in the home increases the risk of sexual victimization (Boney-McCoy & Finkelhor 1995; Kellogg & Menard 2003). In addition, previous studies have noticed that focusing on a single form of violence may overestimate its effects on outcomes. Multiple victimization is known to increase the risk of sexual abuse (Finkelhor et al. 2007a). The first research question in this study examined whether physical, emotional, witnessed, and sibling violence at home increases the risk of child sexual abuse. The second research question examined whether multiple victimizations increase the risk of child sexual abuse. Statistical methods such as logistic regression and the chi-square test were used. A total of 6,825 pupils participated in the Child Victim Survey, of whom 4.5 percent had experienced child sexual abuse by an adult or someone at least five years older. Emotional violence and sibling violence were more often present than absent among victims of sexual abuse. Statistical analysis showed that emotional violence and witnessing violence were statistically significant, increasing the risk of child sexual abuse. Multiple victimization was also statistically significant, increasing the risk of sexual abuse more than 2.2 times. Over 30 percent of sexual abuse victims had two additional victimization experiences beyond the abuse itself. The analyses also demonstrated that children’s risky behaviors, such as alcohol and drug use, increased vulnerability to child sexual abuse. Other risk factors included being a girl, the presence of a disability, disease, or injury, a poor parent–child relationship, parental alcohol use, and family structure. Future research should broaden the concept of violence to include peer violence, community violence, and neglect. It would also be important to extend research to upper secondary students. Continued research is essential to better support children and adolescents in vulnerable situations.

Tämä tutkimus tutkii lisääkö lapseen kohdistuva fyysinen, henkinen, todistettu ja sisarusten välinen väkivalta riskiä tulla seksuaalisesti hyväksikäytetyksi 12–16-vuotiaille Suomessa. Aineisto on vuoden 2022 Lapsiuhritutkimuksesta, joka on kolmas kansallisesti edustava tutkimus kuudes- ja yhdeksäsluokkalaisten väkivalta kokemuksista Suomessa. Oppilaat vastasivat koulupäivän aikana internet kyselyyn, jossa tiedusteltiin, minkälaisia uhrikokemuksia oppilaat ovat kokeneet kotona, koulussa, harrastuksissa ja vapaa-ajalla. (Mielityinen ym. 2023.) Aiemmin aihetta on tutkittu enemmän aikuisilla takautuvasti ja vain vähän tutkimusta on tehty selvittäen lapsilta heidän uhrikokemuksiansa (Felitti ym. 1998; Ports ym. 2016; Andersen ym. 2024). Tutkimus on merkittävä myös, sillä tutkimuksessa tutkitaan mahdollisia tulevia riskejä joutua seksuaalisesti hyväksikäytetyksi käyttäen myös muita tunnettuja riskitekijöitä, selvittämään väkivallan todellista riskiä kokonaiskuvassa. Taustateoriana on käytetty Felitti ym. (1998) haitallisten lapsuuden kokemuksiin liittyvä ACE-teoria. ACE-teorian tarkastelee miten kokemukset väkivallasta, laiminlyönnistä ja perheen ongelmista lisäävät riskiä myöhempiin terveys- ja hyvinvointiongelmiin. Teorian mukaan mitä enemmän haitallisia kokemuksia lapsella on, sitä suurempi todennäköisyys pitkäaikaisille haitoille. Aiemmat takautuvat tutkimukset ovat löytäneet väkivallan kotona lisäävän riskiä tulla seksuaalisesti hyväksikäytetyksi (Dong et al. 2003; Finkelhor ym. 2007b; Zurbriggen ym. 2010; Briere ym. 2020). Myös lapsilla tehdyt tutkimukset ovat todenneet väkivallan kotona lisäävän riskiä tulla seksuaalisesti hyväksikäytetyksi (Boney-McCoy & Finkelhor 1995; Kellogg & Menard 2003). Näiden lisäksi aiemmissa tutkimuksissa on havaittu, että yksittäisen väkivallan muodon tutkiminen voidaan yliarvioida sen vaikutusta lopputuloksiin. Moninkertaisten uhrikokemusten tiedetään lisäävän riskiä tulla seksuaalisesti hyväksikäytetyksi. (Finkelhor ym. 2007a.) Tämän tutkimus ensimmäinen tutkimuskysymys selvitti lisääkö fyysinen, henkinen, todistettu ja sisarusten välinen väkivalta kotona riskiä tulla seksuaalisesti hyväksikäytetyksi. Toinen tutkimuskysymys selvitti lisääkö moninkertaiset uhrikokemukset riskiä tulla seksuaalisesti hyväksikäytetyksi. Tutkimuksessa käytettiin tilastollisia analyysimenetelmiä, kuten logistista regressiota ja khii neliön- testiä. Lapsiuhritutkimukseen vastasi 6825 oppilasta, josta 4.5 prosenttia oli kokenut seksuaalista hyväksikäyttöä aikuiselta tai viisi vuotta vanhemmalta henkilöltä. Henkinen ja sisarusten välinen väkivalta oli prosentuaalisesti useimmiten seksuaalisen hyväksikäytön uhreilla läsnä kuin oli poissa. Tilastollinen analyysi osoitti, että henkinen väkivalta ja väkivallan todistaminen olivat tilastollisesti merkitseviä, lisäten seksuaalisen hyväksikäytön riskiä. Myös moninkertainen uhrikokemus oli tilastollisesti merkitsevä, lisäten seksuaalisen hyväksikäytön riskiä yli 2.2 kertaiseksi. Yli 30 prosentilla seksuaalisen hyväksikäytön uhreilla oli 2 uhrikokemusta hyväksikäytön lisäksi. Analyysit myös todistivat lapsen riskikäyttäytymisen, kuten alkoholin ja huumeiden käytön lisäävän riskiä seksuaaliselle hyväksikäytölle. Muita riskitekijöitä oli tytön sukupuoli, lapsen sairaus, vamma tai erityistarve, lapsen ja vanhemman välinen huono suhde, vanhempien alkoholinkäyttö ja perherakenne lisäsivät riskiä seksuaaliselle hyväksikäytölle. Jatkotutkimuksissa olisi tärkeä laajentaa väkivallan käsitettä koskemaan myös kavereiden välistä väkivaltaa, yhteisöllistä väkivaltaa tai lapsen laiminlyöntiä. Tutkimus olisi myös tärkeä laajentaa koskemaan toiseen asteen opiskelijoita. Aiheen tutkimista on tärkeä jatkaa, jotta voidaan paremmin auttaa haavoittuvassa asemassa olevia lapsia ja nuoria.
Keywords: child abuse, child sexual abuse, child emotional abuse, child physical abuse, witnessing violence, sibling violence, multiple victimizations, polyvictimization, Adverse Childhood Experiences, Child Victim Survey, Finland